Labour Supply Effects of a Subsidised Old-Age Part-Time Scheme in Austria - Nikolaus Graf; Helmut Hofer; Rudolf Winter-Ebmer (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2009)
In this paper we evaluate the impact of the old-age part-time scheme (OAPT) on the Austrian labour market which was a policy to allow flexible retirement options for the elderly with an aim to increase labour supply. According to our matching estimates employment probability increases slightly, especially in the first two years after entrance into the programme. Furthermore, the programme seems to reduce the measured unemployment risk. However, the total number of hours worked is significantly reduced by OAPT. While the policy is meant to reduce early exit from the labour force by allowing part-time work, our analysis indicates that most workers substitute part-time work for full-time work and thus the overall effect is rather negative.
Keywords: C31; J14; J26; 330; evaluation of labour market programmes; labour supply of the elderly; nearest neighbour matching